Barista And Mixology Business Development Training For The Student Community In Barelang Prison, Batam City - Dailami; Thamdzir, Moh.; Sukmamedian, Haufi; Irwansyah Rezeki, Syailendra Reza; Ulum Lubis, Taufik Bachrul (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
The Barista and Mixology Business Development Training is a program designed to teach participants basic and advanced skills in two main areas: barista (coffee preparation) and mixology (preparation of alcoholic and non-alcoholic beverages). The main objective is to improve the quality and expertise in managing and developing businesses in these sectors. This training typically covers various topics, such as Barista Skills, Espresso coffee-making techniques, Latte art (the art of creating pictures on coffee with milk), Introduction to different types of coffee and how to choose them, Techniques for serving and interacting with customers, Mixology, Fundamentals of beverage preparation (both alcoholic and non-alcoholic), Combining ingredients and drink recipes, Aesthetics and presentation of beverages, Compliance with regulations in the beverage industry, Business Management, Business planning and marketing strategies, Inventory and cost management, Interpersonal skills and customer service. The participants of this training usually include business owners, managers, or individuals interested in starting or improving their business in the coffee and beverage industry. This training can be conducted in the form of intensive workshops, seminars, or long-term courses, depending on the organizer and the program's objectives.